Assessing the Role of Gender in Shaping Perceptions of Socio- Economic Issues in the Context of Sustainable Local Development: A Study on Respondents' Influence - Hübel (Anghel), Ștefania-Rodica; Stan, Mari-Isabella; Tasențe, Tănase (Technium Sustainability, 2023)
This paper investigates how respondents' gender influence perceptions of socioeconomic issues within the context of Sustainable Local Development (SLD). The study utilizes a structured questionnaire distributed to 216 participants. The analysis reveals that gender significantly shape participants' perspectives on various aspects of their lives, such as quality of life, future expectations, and attitudes towards societal and economic structures. However, the influence of this demographic variable varies across different areas, pointing to a complex and nuanced interplay. In conclusion, the paper suggests that understanding these perceptual differences can contribute to developing socially inclusive and responsive strategies for SLD, hence underlining the need for a continued exploration of these relationships.